Flow field induced particle accumulation inside droplets in rectangular channels1. Issue 13 (7th July 2015) - Hein, Michael; Moskopp, Michael; Seemann, Ralf
<x xml:space="preserve">Abstract</x> We present accumulation of sedimenting particles/cells within elongated droplets. Particle patterns evolve with droplet velocity, as explained by a topological change of the internal flow and the droplet's outer shape.